How do you solve #3x – 2y = 26# and #-7x + 3y = -49# using substitution?

Answer 1

#x = 4#
#y =-7#

Solve by simultaneous equations:

#3x - 2y = 26# #-7x+3y = -49#
Rearrange #3x - 2y = 26# to make #x# the subject of the equation:
#3x = 26 + 2y# #x = (26 + 2y) / 3#
Substitute the value of #x# into #-7x+3y = -49#: #-7*((26 + 2y) / 3) + 3y = -49# #-7*(26/3 + (2y)/3) + 3y = -49#
Multiply out the brackets: #-182/3 + -(14y)/3 + 3y = -49#
Rearrange and place like terms together: #-(14y)/3 + 3y = -49 + 182/3#

Simplify and solve for y:

#-(5y)/3 = 35/3# #-5y = 35/3 *3# #-5y = 35# #y = 35 / -5# #y = -7#

Use value of y to subsitute into any of the two original equations and solve for x:

#3x - 2y = 26# #3x - 2*(-7) = 26# #3x + 14 = 26# #3x = 26 - 14# #3x = 12# #x = 12/3# #x = 4#
Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 2

To solve the system of equations using substitution, follow these steps:

  1. Solve one of the equations for one variable.
  2. Substitute the expression obtained in step 1 into the other equation.
  3. Solve the resulting equation for the remaining variable.
  4. Substitute the value found in step 3 back into one of the original equations to solve for the other variable.
  5. Check the solution by substituting the values of both variables into both original equations.

Let's solve the system of equations:

  1. From the first equation, solve for x: 3x - 2y = 26 => 3x = 26 + 2y => x = (26 + 2y) / 3

  2. Substitute the expression for x into the second equation: -7x + 3y = -49 => -7((26 + 2y) / 3) + 3y = -49

  3. Solve for y: -7((26 + 2y) / 3) + 3y = -49 => -7(26 + 2y) + 9y = -147 => -182 - 14y + 9y = -147 => -5y = 35 => y = -7

  4. Substitute y = -7 into one of the original equations. Let's use the first equation: 3x - 2(-7) = 26 => 3x + 14 = 26 => 3x = 26 - 14 => 3x = 12 => x = 4

  5. Check the solution by substituting x = 4 and y = -7 into both original equations: For the first equation: 3(4) - 2(-7) = 26 12 + 14 = 26 (True) For the second equation: -7(4) + 3(-7) = -49 -28 - 21 = -49 (True)

Therefore, the solution to the system of equations using substitution method is x = 4 and y = -7.

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer from HIX Tutor

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

Not the question you need?

Drag image here or click to upload

Or press Ctrl + V to paste
Answer Background
HIX Tutor
Solve ANY homework problem with a smart AI
  • 98% accuracy study help
  • Covers math, physics, chemistry, biology, and more
  • Step-by-step, in-depth guides
  • Readily available 24/7